Design of an optimized PID controller for non-minimum phase system with delay - Yadav S.; Verma S.K.; Nagar S.K. (My University, 2025)
In this paper an optimized proportional plus integral plus derivative (PID) controller is designed to control the non-minimum phase systems (NMP) with delay. The problem associated with the NMP system is the undershoot behaviour of the system caused by zeros of the right half plane and it becomes trivial as delay increases. To improve the system performance the parameters of the PID controller are optimized using grey wolf optimizer (GWO). The GWO algorithm seeks to obtain the global optimal values of the PID controller in the region delineate by the conventional tuning criterion like Ziegler-Nichols (ZN) rule. The parameters are optimized on the basis of minimizing the integral absolute error (IAE) of the system. Simulation results prove that the proposed method advances the transient performance like settling time, rise time, peak time and overshoot of the system. © 2015 IEEE.